ANATOMI DAUN DAN STATUS KEDUDUKAN TAKSONOMI LUISIA LATIPETALA - SULISTIARINI, DIAH (Research Center for Biology-Indonesian Institute of Sciences, 1986)
DIAH SULlSTIARINI. 1986, Leaf anatomy and the taxonomy status of Luisia latipetala. Berita Biologi 3(4) : 143 - 145.- In the recent publications, Luisia latipetala J. J. S. has always been considered as a synonym of L. zollingeri Reichenb. f. Based on an investigation of the leaf anatomy of 12 herbarium specimens (position, frequency and size of the stomata, guard cell and epidermis arrangement, sclereid distribution and cutin layer countour) it is concluded that the two species should be regarded as separate species.